Use of platelet transfusions prior to lumbar punctures or epidural anaesthesia for the prevention of complications in people with thrombocytopenia - Estcourt, L; Ingram, C; Doree, C; Trivella, M; Stanworth, S (John Wiley and Sons, Ltd, 2016)
Background People with a low platelet count (thrombocytopenia) often require lumbar punctures or an epidural anaesthetic. Lumbar punctures can be diagnostic (haematological malignancies, epidural haematoma, meningitis) or therapeutic (spinal anaesthetic, administration of chemotherapy). Epidural catheters are placed for administration of epidural anaesthetic. Current practice in many countries is to correct thrombocytopenia with platelet transfusions prior to lumbar punctures and epidural anaesthesia, in order to mitigate the risk of serious procedure-related bleeding. However, the platelet count threshold recommended prior to these procedures varies significantly from country to country. This indicates significant uncertainty among clinicians of the correct management of these patients. The risk of bleeding appears to be low but if bleeding occurs it can be very serious (spinal haematoma). Therefore, people may be exposed to the risks of a platelet transfusion without any obvious clinical benefit. Objectives To assess the effects of different platelet transfusion thresholds prior to a lumbar puncture or epidural anaesthesia in people with thrombocytopenia (low platelet count). Search methods We searched for randomised controlled trials (RCTs) in CENTRAL (The Cochrane Library 2016, Issue 3), MEDLINE (from 1946), EMBASE (from 1974), the Transfusion Evidence Library (from 1950) and ongoing trial databases to 3 March 2016. Selection criteria We included RCTs involving transfusions of platelet concentrates, prepared either from individual units of whole blood or by apheresis, and given to prevent bleeding in people of any age with thrombocytopenia requiring insertion of a lumbar puncture needle or epidural catheter. We only included RCTs published in English. Data collection and analysis We used standard methodological procedures expected by Cochrane. Main results We identified no completed or ongoing RCTs in English. We did not exclude any completed or ongoing RCTs because they were published in another language. Authors' conclusions There is no evidence from RCTs to determine what is the correct platelet transfusion threshold prior to insertion of a lumbar puncture needle or epidural catheter. There are no ongoing registered RCTs assessing the effects of different platelet transfusion thresholds prior to the insertion of a lumbar puncture or epidural anaesthesia in people with thrombocytopenia. Any future RCT would need to be very large to detect a difference in the risk of bleeding. We would need to design a study with at least 47,030 participants to be able to detect an increase in the number of people who had major procedure-related bleeding from 1 in 1000 to 2 in 1000.